Schwingungseigenschaften des TeO₄²⁻-Ions - Baran, Enrique José (1978)
A complete assignment of the fundamental vibrations of the tetrahedral TeO₄²⁻ ion is proposed and its principal force constants have been calculated using the modified valence force field. Mean amplitudes of vibration and bond orders are also estimated. The results are briefly discussed and some comparisons with related species are made.